Identifikasi Ragam Jenis Jamur di Taman Buah Lokal Mekar Lestari - Candra Pratama; Amalia Rezeki; Ferry F. Hoesain (Biota, 2023)
Mekar Lestari Local Fruit Park is a park managed by the Indonesian Center for Biodiversity Studies and Conservation. This park has a collection of local fruit plants located in Anjir Muara, Barito Kuala Regency. One of the potential organisms found in this area is fungi. The purpose of this study was to identify the types of fungi in the local fruit garden area "Mekar Lestari" using the exploration method with the selected sample technique. The data obtained were then analyzed by descriptive method. Based on the results of research that has been carried out in the forest in the local fruit garden area "Mekar Lestari" found 15 species of fungi namely Arcyria cinerea, Calocera cornea, Daldinia concentrica, Marasmius siccus, Physarum polycephalum, Physarum album, Volvariella sp, Trametes sanguine, Trametes ochracea, Schizophyllum commune, Collybia cookie, Xylaria polymorpha, Scleroderma cepa, Auricularia sp, and Ductifera pululahuana. The types of fungi found in this study are divided into 12 families and 13 genera. The environmental conditions of the study site were temperature 30.2-37.7 °C, air humidity 77.0-84.8%, light intensity 198-2460 lux and soil pH 6.3-7. The fungi found generally live on decaying wood and litter, and a small proportion live attached to trees